DISASTER RESPONSE MODELING BASE ON LANDSLIDE EARLY WARNING USING CASE MANAGEMENT MODEL AND NOTATION - Sarah Ayu Ekamas; Hanson Prihantoro Putro; Teduh Dirgahayu (Informatika, Universitas Jenderal Soedirman, 2022)
There are a few handling steps in the emergency response to landslides that need thorough explanation. The flexibility of emergency response situations is ineffectively supported by traditional modeling methodologies because they are excessively inflexible. Companies have traditionally modeled their business processes using the Business Process Management Approach and Notation (BPMN) model. For design case management, such as the emergency reaction to a landslide disaster, BPMN modeling is unsuitable. because the BPMN modeling focuses how business processes flow inside a company. The Case Management Model and Notation (CMMN), the newest modeling approach from the Object Management Group (OMG), was launched in 2013 with the purpose of completing the BPMN modeling approach. The unstructured and adaptable CMMN claims to be able to handle urgent situations. This study's intention is to develop a CMMN model of a landslide emergency reaction scenario based on an emergency alert from an Early Warning System (EWS) sensor. In order to acquire the qualitative data for this study, the researcher first conducted a literature review. Then used the interview and observation methods to gather data, and from this data, we created the model using the CMMN modeling approach. The Yogyakarta Special Region Disaster Management Agency's (BPBD DIY) data flow of a disaster management information system, which was already operational, was analyzed by researchers. Then, the researchers used CMMN to model the data in order to find out opportunities to improve the disaster management information system already in use at BPBD DIY. Two CMMN models—the BPBD DIY disaster management information system model and the recommendation model for system improvements—were created in this study. The analysis of the current disaster management information system model resulted in the recomendation of this model. A prototype of feature recommendation is created as part of this research and given to specialists in natural disasters for model validation.